Scavenging 4-Oxo-2-nonenal - Amarnath, Venkataraman (Chem Res Toxicol, 2015)
4-Oxo-2-nonenal (ONE), a product of cellular lipid oxidation, reacts nonspecifically with the lysine residues of proteins and is generated in increased amounts during degenerative diseases and cancer. We show that pyridoxamine, salicylamine, and related 2-aminomethylphenols react with ONE, to form pyrrolo[2,1-b][1,3]oxazines with the participation of both the amino and the phenolic groups. 2-Aminomethylphenols react with ONE as well as with the Michael adducts of ONE much more rapidly than lysine, suggesting their use for therapeutically scavenging ONE.